Śrī Sevaka vāṇī : vyākhyā sahita - Dāmodaradāsa, fl. 1520-1553 (Veṇu Prakāśana, 1975)
Verse work, with commentary, on the life and teachings of Hita Harivaṃśa Gosvāmī, 1502-1552, exponent of the Rādhavāllabha sect in Vaishnavism.